Odpowiedzi

2010-02-07T19:21:24+01:00
A) = abc - abc + xyz - xyz - abc = -abc
b) = s²t - st² - s²t - st² - s²t = -s²t
c) = x²yz - xy²z - xyz² - x²yz - xy²z = -xyz²
;))
2 1 2
2010-02-07T19:23:57+01:00
A) abc- (abc - ( -xyz - (xyz - abc)))
= abc - (abc - ( -xyz - xyz + abc))=
= abc - (abc +xyz + xyz - abc)=
= abc - abc -xyz - xyz + abc=
=-2xyz+abc

b) s²t - ( st² - (s²t - (st² - s²t )))
=s²t - ( st² - (s²t - st² +s²t ))=
=s²t - ( st² - s²t + st² -s²t )=
=s²t - st² + s²t - st² +s²t =
= 3s²t- 2st²

c) x² yz - (xy² z - (xyz² - ( x²yz - xy²z )))
=x² yz - (xy² z - (xyz² - x²yz + xy²z ))=
=x² yz - (xy² z - xyz² + x²yz - xy²z )=
=x² yz - xy² z + xyz² - x²yz + xy²z =
=xyz²
2 5 2
2010-02-07T19:30:23+01:00
A) abc- (abc - ( -xyz - (xyz - abc)))=abc-(abc-(-xyz-xyz+abc))=
=abc-(abc+xyz+xyz-abc)=abc-abc-xyz-xyz+abc=-2xyz+abc
b) s²t - ( st² - (s²t - (st² - s²t )))=s²t-(st²-(s²t-st²+s²t))=
=s²t-(st²-s²t+st²-s²t)=s²t-st²+s²t-st²+s²t=3s²t-2st²
c) x² yz - (xy² z - (xyz² - ( x²yz - xy²z )))=x²yz-(xy²z-(xyz²-x²yz+xy²z))=x²yz-(xy²z-x²yz+x²yz-xy²z)=
=x²yz-xy²z+x²yz-x²yz+xy²z=x²yz
1 5 1